Cholinergic receptor nicotinic alpha 5 subunit polymorphisms are associated with smoking cessation success in women - Paulo Roberto Xavier Tomaz; Juliana Rocha Santos; Jaqueline Scholz; Tânia Ogawa Abe; Patrícia Viviane Gaya; André Brooking Negrão; José Eduardo Krieger; Alexandre Costa Pereira; Paulo Caleb Júnior Lima Santos (BMC, 2018)
Abstract Background The identification of variants in the nicotinic acetylcholine receptor (nAChR) subunit genes associated with smoking phenotypes are increasingly important for prevention and treatment of nicotine dependence. In the context of personalized medicine, the aims of this study were to evaluate whether cholinergic receptor nicotinic alpha 2 (CHRNA2), cholinergic receptor nicotinic alpha 3 (CHRNA3), cholinergic receptor nicotinic alpha 5 (CHRNA5) and cholinergic receptor nicotinic beta 3 (CHRNB3) polymorphisms were associated with nicotine dependence severity, and to investigate possible pharmacogenetics markers of smoking cessation treatment. Methods This study cohort enrolled 1049 smoking patients who received pharmacological treatment (varenicline, varenicline plus bupropion, bupropion plus/or nicotine replacement therapy). Smoking cessation success was considered for patients who completed 6 months of continuous abstinence. Fagerström test for nicotine dependence (FTND) and Issa situational smoking scores (Issa score) were analyzed for nicotine dependence. CHRNA2 (rs2472553), CHRNA3 (rs1051730), CHRNA5 (rs16969968 and rs2036527) and CHRNB3 (rs6474413) polymorphisms were genotyped by high resolution melting analysis. Results Females with GA and AA genotypes for CHRNA5 rs16969968 and rs2036527 polymorphisms had higher success rate in smoking cessation treatment: 44.0% and 56.3% (rs16969968), 41.5% and 56.5% (rs2036527), respectively, compared with carriers of the GG genotypes: 35.7% (rs16969968), 34.8% (rs2036527), (P = 0.03, n = 389; P = 0.01, n = 391). The GA or AA genotypes for the rs16969968 and rs2036527 were associated with higher odds ratio for success in women (OR = 1.63; 95% CI = 1.04 to 2.54; P = 0.03 and OR = 1.59, 95% CI = 1.02 to 2.48; P = 0.04; respectively). We did not find association of these polymorphisms with nicotine dependence related scores. Polymorphisms in the CHRNA2, CHRNA3 and CHRNB3 genes were not associated with the phenotypes studied. Conclusion CHRNA5 rs16969968 and rs2036527 were associated with higher success rate in the smoking cessation treatment in women. These findings might contribute to advances in personalized medicine.